(untitled) (Scientific journal of the Fergana State University, 2026)
Critical thinking constitutes an essential component of contemporary language education. This article examines the pedagogical potential of developing language learners’ critical thinking skills through Kohlberg‘s theory of moral development. The research reveals the interconnection between moral reasoning and the language learning process. The article demonstrates methods for enhancing students’ abilities in critical evaluation, independent thinking, and ethical decision-making by applying Kohlberg‘s six-stage model within the language classroom context. Practical recommendations and curriculum design suggestions are provided for language educators.